PENGARUH PEMBERIAN REWARD DAN PUNISHMENT TERHADAP MOTIVASI BELAJAR IPS SISWA KELAS VIII DI SMPN 29 PEKANBARU - Welly Octaviani; Gimin Gimin; Hendripides Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study purpose to determine the influence of reward and punishment on learning motivation IPS class VIII students in SMPN 29 Pekanbaru. The population in this study is all students of class VIII, amounting to 254 students with a sample of 72 students. Data collection techniques used are questionnaires. The data analysis used is multiple linear regression. The result of research based on multiple linear regression has shown reward and punishment influence to motivation study of IPS student of class VIII at SMPN 29 Pekanbaru. Reward positive effect on learning motivation and punishment have negative effect on learning motivation, this can be seen from constant value (a) equal to 32,329, regression coefficient value (b) equal to 0,782, and regression coefficient (c) equal to -0,537 with regression equation 32,329+ 0.782R - 0.537P. Judging from the calculation of R2 (R Square Change) obtained value of 0.703. This means that the percentage contribution of reward and punishment variable to the variable of learning motivation is 70,3%. Based on these results, it is suggested that teachers improve reward and punishment to increase learning motivation. However, giving punishment to students who have low learning motivation should be wise and in accordance with the mistakes made by these students.Keywords: Reward, Punishment, Learning Motivation.